The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.35943/mvmj.2020.21.108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, molecular characterization, virulotyping, and antibiotic resistance of motile aeromonads isolated from Nile tilapia farms at northern Egypt

Abstract: Objective: This study was aimed to survey Aeromonas spp associated with cultured Nile tilapia Oreochromis niloticus (O. niloticus) showing signs of motile Aeromonas septicemia (MAS) at different fish farms; molecular characterization and identification of test isolates; and to test the isolates for their antimicrobial and virulence activities that contribute to its pathogenesis. Design: Observational study Animals: 280 Nile tilapia Procedures: Clinically diseased 280 Nile tilapia, were collected from differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
3
6
0
Order By: Relevance
“…These findings are related to the poor water quality parameters evaluated in the examined farms, as the highest aeromonads prevalence was noticed in farm IV and farm III, particularly in August and June. These present findings are consistent with other studies reported elsewhere [ 50 , 53 ]. Taken into account, the highest prevalence of Aeromonas during summer could be attributed to improper water quality parameters as measured herein, where shifting from normal ranges poses stress on fish with subsequent lowering in their resistance to bacterial infections [ 50 , 54 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…These findings are related to the poor water quality parameters evaluated in the examined farms, as the highest aeromonads prevalence was noticed in farm IV and farm III, particularly in August and June. These present findings are consistent with other studies reported elsewhere [ 50 , 53 ]. Taken into account, the highest prevalence of Aeromonas during summer could be attributed to improper water quality parameters as measured herein, where shifting from normal ranges poses stress on fish with subsequent lowering in their resistance to bacterial infections [ 50 , 54 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our findings were consistent with previous studies that showed similar histopathological lesions due to MAS [81][82][83]. These observations were supportive to the motile aeromonads virulence genes herein, as well as the extracellular products, enzymes, and enterotoxins produced by motile aeromonads that together led to a systemic damage to the internal organs, mainly, liver, kidney and spleen with eventual death [9,50,67,81].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, another study reported a lower rate of 66.7% [90]. For instance, in another study, the prevalence of the aerA gene was high (83.3%) and that of the ahh1 gene was low (16.7%) [91].…”
Section: Discussionmentioning
confidence: 92%